(untitled) (Raparin Journal of Humanities (RJH), 2024)
Islamic banks, since their inception, have been working to provide financial services to Muslims in particular, as these services must comply with the provisions of Islamic law, and among the most important institutions that request financial services from banks and are in dire need of that are companies of all kinds and forms, and in most cases, companies rely on Its capital and cash flow to banks to facilitate the management of its various activities, and Islamic companies cannot deal with conventional banks; So, these services are requested from Islamic banks, and the services of Islamic banks are the same as the services of traditional banks, but with a jurisprudential adaptation or by using the exits to get out of the distress of usury, and from the distress of the need for real action for it, and according to the companies’ request and needs, the banks find exits and solutions to meet their request by the principles and rules of Sharia. Islamic and satisfy the desires of companies, and the process of evaluation of these adaptations is one of the necessary things in this era; Accordingly, the researchers tried to evaluate this adaptation in one of the Islamic banks in part of its various services, which is Kuwait finance house in Malaysia.